Literatuur en religie = Literature and religion - Fraeters, Veerle 1963-; Nuyts, Tijl 1993-; Debergh, Gwennie 1975- (Academia Press, 2020)
In the wake of 9/11, religion has made a comeback as a geopolitical and discursive reality. Literary criticism and theory too are turning increasingly towards religion in the cultural production of the present and past. This issue of CLW pays attention to a vast array of literary traditions, confessions and methodological perspectives, with topics ranging from modern Zen Buddhist autobiographies to the Jewish urban novel, and from the vagaries of a Bible motif to Sufi motifs in German literature.
Keywords: Geschichte 1900-2020; Literatur; Religion -- Motiv; Aufsatzsammlung